A 12 kW three-phase low THD rectifier with high-frequency isolation and regulated DC output - de Seixas, FJM; Barbi, I (Institute of Electrical and Electronics Engineers (IEEE), 2004)
A robust 12 kW rectifier with low THD in the line currents, based on an 18-pulse transformer arrangement with reduced kVA capacities followed by a high-frequency isolation stage is presented in this work. Three full-bridge (buck-based) converters are used to allow galvanic isolation and to balance the dc-link currents, without current sensing or current controller. The topology provides a regulated dc output with a very simple and well-known control strategy and natural three-phase power factor correction. The phase-shift PWM technique, with zero-voltage switching is used for the high-frequency dc-dc stage. Analytical results from Fourier analysis of winding currents and the vector diagram of winding voltages are presented. Experimental results from a 12 kW prototype are shown in the paper to verify the efficiency, robustness and simplicity of the command circuitry to the proposed concept.
Keywords: AC-DC converter; autotransformer; 18-pulse; harmonics; high-frequency conversion; power factor correction